Expanding the spatial scale in DNA-based monitoring schemes: ascertainment bias in transnational assessments - Kopatz, Alexander; Norman, Anita J.; Spong, Göran; Valtonen, Mia; Kojola, Ilpo; Aspi, Jouni; Kindberg, Jonas; Flagstad, Øystein; Kleven, Oddmund (Springer Nature, 2024)
Harmonising methodology between countries is crucial in transborder population monitoring. However, immediate application of alleged, established DNA-based methods across the extended area can entail drawbacks and may lead to biases. Therefore, genetic methods need to be tested across the whole area before being deployed. Around 4,500 brown bears (Ursus arctos) live in Norway, Sweden, and Finland and they are divided into the western (Scandinavian) and eastern (Karelian) population. Both populations have recovered and are connected via asymmetric migration. DNA-based population monitoring in Norway and Sweden uses the same set of genetic markers. With Finland aiming to implement monitoring, we tested the available SNP-panel developed to assess brown bears in Norway and Sweden, on tissue samples from a representative set of 93 legally harvested individuals from Finland. The aim was to test for ascertainment bias and evaluate its suitability for DNA-based transnational-monitoring covering all three countries. We compared results to the performance of microsatellite genotypes of the same individuals in Finland and against SNP-genotypes from individuals sampled in Sweden (N = 95) and Norway (N = 27). In Finland, a higher resolution for individual identification was obtained for SNPs (PI = 1.18E-27) compared to microsatellites (PI = 4.2E-11). Compared to Norway and Sweden, probability of identity of the SNP-panel was slightly higher and expected heterozygosity lower in Finland indicating ascertainment bias. Yet, our evaluation show that the available SNP-panel outperforms the microsatellite panel currently applied in Norway and Sweden. The SNP-panel represents a powerful tool that could aid improving transnational DNA-based monitoring of brown bears across these three countries.
Keywords: noninvasive sampling; single-nucleotide sampling; DNA-based transborder monitoring; genetic methods; microsatellites